ANALISA INVESTASI KEUANGAN DAN PENGARUHNYA TERHADAP KINERJA PERUSAHAAN SEKTOR PERHOTELAN - Hidayat, Taufik (Emerging Markets : Business and Management Studies Journal, 2018)
The study was conducted to analyze the hotel performance focusing on the financial aspect. This is critical for the hotel since they have done building renovation financed by the bank, therefore controlling the financial activities will assist the hotel debt return in the long run. The financial analysis used some tools such as Break Event Point (BEP), Internal Rate of Return (IRR), Revenue Cost Ratio (RCR), Return On Investment (ROI), Return On Equity (ROE), Cost Benefit Ratio (CBR) dan Profitability Index to measure the hotel?s performance. The result shows that NPV> 0 then investment with NPV Rp. 39.36 billion can be continued safely. The Break event point (BEP) is accepted for 8 years. The Internal Rate of Return (IRR) method is used to analyze the amount of interest that makes the cost of expenditure and income equal to the size of IRR Hotel XYZ 15.87%> 8.5% (interest deposit bank) where IRR> i (interest rate), so investment proposal accepted. The RCR (Revenue Cost Ratio) method is 1.17 in 2012, amounting to 1.20 in 2013 andamounting to 1.38 in 2014 which explains that R / C> 1 is profitable after the project. The ROI (Return on Investment) was explained that there was an increase in the ability of Hotels in obtaining operating profit from invested capital in all assets. ROE (Return on Equity) explained that there was an increase in the ability of XYZ Hotels to obtain net income from paid-up capital. The Profitability Index (PI) method of 1.656> 1 then the building renovation of the hotel can be continued and profitable.